Pelatihan Teknik Pengambilan Data Mangrove Guna Peningkatan Keterampilan Eksplorasi Mahasiswa di Pesisir Teluk Kendari - Arwan Arif Rahman; Laode Muhammad Yasir Haya; Muhammad Ramli; Arman Pariakan; Indrayani Indrayani; Adi Imam Wahyudi (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
The exploration and research abilities of students were substantially enhanced through training in mangrove data collection techniques conducted along the coast of Kendari Bay. The effectiveness of the theoretical sessions and field practice is evidenced by an increase in theoretical understanding scores from 65.8 to 82.4 and practical skills scores from 2.2 to 4.1. The training, which was attended by 45 students, produced a comprehensive database comprising 135 vegetation plots, identification of 12 mangrove species, as well as water quality and substrate data from three locations. In addition to improving technical skills, the training facilitated the formation of study groups and the development of collaborative research proposals, which in turn increased motivation and research collaboration among participants. The resulting data have been submitted to the Kendari City Environmental Agency as a foundation for mangrove management. The success of this program demonstrates that experience-based methodologies are effective in enhancing human resource capacity and supporting the sustainable conservation of mangrove ecosystems.